Eksplorasi Keragaman Morfologi dan Karakter Penciri Tanaman Kopi Lokal “Tuni” di Kabupaten Seram Bagian Barat, Maluku - Andi Ardiansyah; Asri Subkhan Mahulette; Abdul Karim Kilkoda (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
West Seram Regency is one of the regions supplying local Tuni coffee in Maluku. Until now, information on the morphological diversity and characteristics of local Tuni coffee in West Seram Regency has not been widely reported. This study aims to analyze the morphological diversity and characteristics of local Tuni coffee plants in West Seram Regency. Morphological characterization was carried out in several distribution locations of local Tuni coffee in West Seram Regency, including: Kairatu Village, Nuruwe Village, Waesamu Village, Tanah Goyang Hamlet, Piru Village, and South Buano Village. Morphological diversity characterization was carried out on 50 samples of local Tuni coffee plants, using the modified "International Plant Genetic Resources Institute" coffee descriptor guide. The results of Hierarchical Cluster Analysis (HCA) based on 67 morphological characters obtained two groups with a dissimilarity coefficient of 14.50%. The first group consisted of 10 accessions clustered with a similarity of 86.70%, while the second group consisted of 40 accessions with a dissimilarity coefficient of 9.70%. The second group was further divided into two groups: group II-a, comprising 15 accessions with a similarity coefficient of 90.30%, and group II-b, comprising 25 accessions with a similarity coefficient of 89.10%. The results of Principal Component Analysis (PCA) based on 34 characters obtained a total variation of 43.5%. The identified characteristics of local Tuni coffee were the number of branches, leaf width, leaf area, number of petals per flower, flower length, ripe fruit thickness, semi-ripe fruit weight, ripe bean length, and semi-ripe bean diameter.